Audit Energi dan Analisis Peluang Penghematan Energi di PT. Daikin Air Conditioning Makassar - Purwito, Purwito; Tadjuddin, Tadjuddin; Akbar, Akbar (INTEK: Jurnal Penelitian, 2018)
Energy audit is an activity to identivy how muchenergy is used as well as the steps that are needed in order toconcerve energy on an energy user facility. PT. Daikin AirConditioning Makassar using air conditioning equipments thatuses electrical energy nearly 60%. This study aims to determinethe used of electrical energy and energy saving opportunities inPT. Daikin Air Conditioning Makassar. Reseacrh is started withprocessing of electrical equipment data for lighting, airconditioning and other electrical equipments data. Researchresult pointed that the used of electric energyin PT. Daiking AirConditioning Makassar is 111.3 kWh/m2 /year and still below thestandart of IKE and can be savingabout 44 kWH/month forlighting system. Recommendations are to perform load balancingeach phase, turn on the light and air condioning only whenneeded.